THE CORELLATION OF USING ENGLISH SLANG ABBREVIATIONS ON STUDENTS WRITING DESCRIPTIVE TEXT AT SMA DARUL ABROR - Khoirunnisa (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
This research aims to determine whether there is a correlation between the use of English slang and writing descriptive texts in eleventh grade at SMA Darul Abror. This method in this research uses a casual associative quantitative method, namely method for obtaining data naturally from certain places. In the research, researchers carry out treatments to collect data, for example distributing questionnaires and conducting tests. To as certain the cause and effect link between independent variables (variables that influenced) and dependent variables (variables that are influenced) associative quantitative research is also conducted. The associative quantitative research technique is chosen based on how well the approach fits the study title, which seeks to understand the relationship between the dependent variable (writing descriptive text) and the independent variable (English slang). The usage of English slang and students’ capacity to produce descriptive writings in English slang learning at SMA Darul Abror are related, according to the analysis of the research findings. There is a link between the usage of English slang and pupils’ ability to write at a moderate level. A substantial connection between the two variables is shown by a correlation coefficient, or ‘r’, of 0.473 and a significance value (p-value) of 0.020. As a result, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is supported, showing that students’ capacity to produce descriptive texts is favorably impacted by the usage of English slang.